Adiposity and the development of dyslipidemia in APOE ε2 homozygous subjects: A longitudinal analysis in two population-based cohorts. (May 2021) - Heidemann, Britt E.; Wolters, Frank J.; Kavousi, Maryam; Gruppen, Eke G.; Dullaart, Robin PF.; Marais, A. David; Visseren, Frank LJ.; Koopal, Charlotte
Abstract: Background and aims: Familial dysbetalipoproteinemia (FD), characterized by remnant lipoprotein accumulation and premature cardiovascular disease, occurs in homozygous carriers of the APOE ε2 allele, but genetic predisposition alone does not suffice for the clinical phenotype. Cross-sectional studies suggest that a second metabolic hit – notably adiposity or insulin resistance – is required, but the association between these risk factors and development of FD has not been studied prospectively. Methods: For this study, we evaluated 18, 987 subjects from two large prospective Dutch population-based cohorts (PREVEND and Rotterdam Study) of whom 118 were homozygous APOE ε2 carriers. Of these, 69 subjects were available for prospective analyses. Dyslipidemia – likely to be FD – was defined as fasting triglyceride (TG) levels >3 mmol/L in untreated subjects or use of lipid lowering medication. The effect of weight, body mass index (BMI), waist circumference, type 2 diabetes mellitus and non-TG metabolic syndrome on development of dyslipidemia was investigated. Results: Eleven of the 69 ε2ε2 subjects (16%) developed dyslipidemia – likely FD – during follow-up. Age-, sex- and cohort-adjusted risk factors for the development of FD were BMI (OR 1.19; 95%CI 1.04–1.39), waist circumference (OR 1.26 95%CI 1.01–1.61) and presence of non-TG metabolic syndrome (OR 4.39; 95%CI 1.04–18.4) at baseline. Change in adiposity during follow-up was not associated with development of dyslipidemia. Conclusions: Adiposity increases the risk of developing an FD-like lipid phenotype in homozygous APOE ε2 subjects. These results stress the importance of healthy body weight in subjects at risk of developing FD. Graphical abstract: Image 1 Highlights: Baseline adiposity increases the risk of developing dyslipidemia – likely familial dysbetalipoproteinemia (FD) – in ε2ε2 subjects from the general population. Change in adiposity during follow-up was not associated with the development of dyslipidemia – likely FD. This suggests that in ε2ε2 subjects the 'switch' to FD-like lipid phenotype is a gradual process that starts early in life.